2019
DOI: 10.1111/1755-0998.13023
|View full text |Cite
|
Sign up to set email alerts
|

Genome analyses of the new model protist Euplotes vannus focusing on genome rearrangement and resistance to environmental stressors

Abstract: As a model organism for studies of cell and environmental biology, the free‐living and cosmopolitan ciliate Euplotes vannus shows intriguing features like dual genome architecture (i.e., separate germline and somatic nuclei in each cell/organism), “gene‐sized” chromosomes, stop codon reassignment, programmed ribosomal frameshifting (PRF) and strong resistance to environmental stressors. However, the molecular mechanisms that account for these remarkable traits remain largely unknown. Here we report a combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 100 publications
11
56
1
Order By: Relevance
“…Interestingly, SMYD homologues of the four ciliates included in this study showed relatively low similarity (in the range of 10.4%-41%). This high diversity of ciliate SMYD is consistent with the fact that ciliates underwent radiation after their early branching and harbored a rich pool of morphological and genetic diversities (Chen et al 2014(Chen et al , 2018(Chen et al , 2019Guerin et al 2017;Hamilton et al 2016;…”
Section: Smyd Homologues In Ciliatessupporting
confidence: 75%
“…Interestingly, SMYD homologues of the four ciliates included in this study showed relatively low similarity (in the range of 10.4%-41%). This high diversity of ciliate SMYD is consistent with the fact that ciliates underwent radiation after their early branching and harbored a rich pool of morphological and genetic diversities (Chen et al 2014(Chen et al , 2018(Chen et al , 2019Guerin et al 2017;Hamilton et al 2016;…”
Section: Smyd Homologues In Ciliatessupporting
confidence: 75%
“…The PCR conditions and primers which were used to amplify the SSU rRNA gene follow previous studies (Chen et al. ; Gao et al. 2016a; Wang et al.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted using a DNeasy Tissue kit (Qiagen, Hilden, Germany). The PCR conditions and primers which were used to amplify the SSU rRNA gene follow previous studies (Chen et al 2019;Gao et al 2016a;Wang et al 2019). PCR products were sequenced without cloning.…”
Section: Dna Extraction Pcr Amplification and Ssu Rrna Gene Sequencingmentioning
confidence: 99%
“…In each cell, a germline micronucleus (MIC), which is inactive during the vegetative life coexists with a somatic polyploid macronucleus (MAC), which controls the general functions of the cell [7]. The genome of the MIC is arranged into typical eukaryotic chromosomes, while the genome of the MAC is composed by centromere-less chromosomes amplified in hundreds of copies [7][8][9][10][11]. Because of these characters, ciliates are used as model organisms in a wide range of disciplines, including cytology, evolutionary biology, and genetics [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%